KEMAMPUAN GERAK MANIPULATIF MAHASISWA PESERTA PERKULIAHAN PERMAINAN NET TAHUN ANGKATAN 2010 - Amat Komari (Jurnal Pendidikan Jasmani Indonesia, 2014)
AbstractThe main objective of this study was to determine the ability of the students participating in the course of motionmanipulative Net Games teaching class of 2010. The research design of this study is descriptive. The variables ofthis study is the ability of the students participating in the course of motion manipulative Net Game teaching in class2010. The population in this study is PJKR students who are taking courses Games Net Teaching is numbered240 students. The sample in this research were 160 students diambel by cluster random sampling technique. Theinstrument used in this study is the shuttlecock juggling test. This test is compiled by the researcher. The validity andreliability of the test results obtained.Validity and reliability of the test results obtained. The validity of the obtainedtest-re-test techniques, and the validity of the test results obtained by correlating the raw instrument. Data analysistechniques used in this research is descriptive Stats further explained by the percentage. Based on the researchresults and conclusions can be seen that the majority of students who take the courses PJKR teaching net gameshave the basic motion manipulative ability is shown by the percentage that reached 63.13%. While students with lowability more numerous when compared with students with basic motion capabilities manipulative Cleaner is equal to20.63% at 16.25% and a low ability to high ability.Keywords: Motion manipulatives, Net GamesAbstrakTujuan utama penelitian ini adalah untuk mengetahui kemampuan gerak manipulatif mahasiswa peserta perkuliahanPengajaran Net tahun angkatak 2010. Desain penelitian dari penelitian ini adalah Deskriptif. Variabel dari penelitianini adalah kemampuan gerak manipulatif mahasiswa peserta perkuliahan Pengajaran Net tahun angkatan 2010.Populasi dalam penelitian ini adalah mahasiswa PJKR yang sedang menempuh mata kuliah Pengajaran PermainanNet yaitu berjumlah 240 mahasiswa. Sampel dalam penelitian ini berjumlah 160 mahasiswa diambil dengan teknikcluster random sampling. Instrumen yang digunakan dalam penelitian ini adalah tes juggling shuttlecock. Tes inidisusun sendiri oleh peneliti. Validitas dan reliabilitas didapatkan dari hasil tes. Validitas didapatkan dengan tekniktest- re test, dan validitas didapatkan dengan mengkorelasikan hasil tes dengan instrumen baku. Teknik analisisdata yang digunakan dalam penelitian ini adalah statistk deskriptif dengan dijelaskan lebih lanjut dengan persentase.Berdasar hasil penelitian dan kesimpulan dapat diketahui bahwa sebagian besar mahasiswa PJKR yang menempuhmata kuliah pengajaran permainan net memiliki kemampuan gerak dasar manipulatif sedang hal ini ditunjukkandengan besaran persentase yang mencapai 63,13%. Sedangkan mahasiswa dengan kemampuan rendah lebihbanyak jumlahnya apabila dibandingkan dengan mahasiswa dengan kemampuan gerak dasar manipulatif yang tingiyaitu sebesar 20,63% pada kemampuan rendah dan 16,25% pada kemampuan tinggi.Kata Kunci: Gerak Manipulatif, Permainan Net